2016
DOI: 10.17795/ajmb.33540
|View full text |Cite
|
Sign up to set email alerts
|

Association of Seminal Plasma Total Antioxidant Capacity and Malondialdehyde Levels With Sperm Parameters in Infertile Men With Varicocele

Abstract: Background: Varicocele is one of the most common reasons for male infertility and could impair spermatogenesis through mechanisms that are not well known. Recently, oxidative stress has been introduced as a major reason for male infertility caused by varicocele.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…With this in mind, the result of total antioxidant capacity (TAC) analysis in the current study revealed significantly lower activity in asthenozoospermic. Our result was similar to Salimi et al [39], and Hosen et al [40] studies established that the total antioxidant capacity value in infertile men was lower than that in fertile men. In addition, Riaz et al .…”
Section: Discussionsupporting
confidence: 93%
“…With this in mind, the result of total antioxidant capacity (TAC) analysis in the current study revealed significantly lower activity in asthenozoospermic. Our result was similar to Salimi et al [39], and Hosen et al [40] studies established that the total antioxidant capacity value in infertile men was lower than that in fertile men. In addition, Riaz et al .…”
Section: Discussionsupporting
confidence: 93%
“…The dosedependent increase in TAC was strongly associated with the progressive rise in sperm cell viability and the decreases in apoptosis, necrosis, and structural abnormalities. Consistent with these findings, Salimi, et al [44] reported positive correlations between TAC and both sperm motility and normal sperm morphology, while Pahune, et al [45] observed positive correlations between TAC and multiple seminogram parameters including sperm concentration, sperm motility, and normal sperm morphology. Collectively, these findings suggest that an imbalance between TAC and ROS production is a major contributor to impaired sperm function following cryopreservation [46].…”
Section: Discussionmentioning
confidence: 64%
“…The total antioxidant capacity (TAC) of seminal plasma was measured using the ferric reducing ability of plasma (FRAP) method as described by Salimi et al (2016). This method is based on the ability of the antioxidants in the seminal plasma to reduce ferric-tripyridyltriazine (Fe 3þ -TPTZ) to a ferrous form (Fe 2þ ).…”
Section: Total Antioxidant Capacity Of Seminal Plasmamentioning
confidence: 99%